Atividades de estudo de física hipermidiáticas: flexibilidade cognitiva, interatividade, interação e visualização - Vidmar, Muryel Pyetro (2013)
The main objective of this research was to investigate the contribution of the educational hypermedia as technological mediation to the development of study activities and, consequently, for the understanding of knowledges treated in the high school of Physics. To do this, we work with the elaboration and analysis of hypermedia study activities, structured in according to the approach contained in the national curriculum guidelines. This process occurred with physicists-educators in initial formation, thus contributing to the future school practices thereof, in scope of the high school. We use as research conception the action-research, which involved the development of cycles characterized by moments of planning, action, observation and reflection. Data collection involved the following instruments: document analysis, questionnaire, and the tools forum, task and wiki from Moodle. The analysis of this data, that occured in the moment of reflection of the action-research, allowed us to conclude that the features potentialized by the educational hypermedia cognitive flexibility, interactivity, interaction and visualization contribute significantly to the development of study activities of Physics, and, with this, for the understanding of the physical knowledges treated in the high school.